Komposisi Senyawa 1.8-cineole dari Ekstrak Daun Eucalyptus pellita Menggunakan 2 Jenis Pelarut serta Fitotoksisitas Terhadap Gulma Borreria alata (Aubl) DC. - Rangkuti, Muhammad Syaid; Hapsoh, Hapsoh; Adiwirman, Adiwirman (LPPM Universitas Muhammadiyah Riau, 2023)
The monoterpene group has a molecule called 1.8-cineole as its primary component. The compound 1.8-cineole is one of the most powerful allelochemicals released by many species, such as Eucalyptus spp., which is toxic to other plants. This study intends to identify a suitable solvent to extract 1.8-cineole derived from Eucalyptus pellita leaf extract using 2 types of solvents, ethanol and aquadest along with their phytotoxicity properties. This research was conducted in 2 stages. The first stage involved the extraction of Eucalyptus pellita leaves using the Soxhlet method, and the extraction results were analyzed with GC/MS. The second stage of the phytotoxicity test against Borreria alata (Aubl) DC., weeds used seven levels of extraction formula treatment. The extraction results using ethanol solvents showed higher yields of 1.8-cineole compound composition compared to using aquadest solvents. The results of the phytotoxicity test of variance showed a significant difference in the wet and dried mass of weeds. The extraction formula with a concentration of 50% Eucalyptus pellita leaf extract using ethanol as a solvent has the best phytotoxicity properties compared to other extraction formulas.